(untitled) (Research, Society and Development, 2022)
Metaplasia is a reversible adaptive process, which occurs in a cell type that, upon a stimulus, undergoes the replacement of another cell type of similar lineage. Objective: to identify the prevalence of metaplasia in esophageal mucosal samples and evaluate the relationship between metaplasia and histopathological lesions. Method: cross-sectional, retrospective study with a sample of 1953 histopathological reports of the esophageal mucosa. Results: from 1953 reports, 548 (28.1%) had metaplasia, 94 (17.1%) of the intestinal type and of these 35 (6.4%) were focal; 133 (6.8%) had Barrett’s esophagus, 414 (75.5%) with gastric ectopia, 21 (1.1%) with dysplasia, 12 (57.1%) with low grade and 9 (42.9 %) high degree and 1427 (73.1%) reports presented esophagitis. The median age group of patients with metaplasia was 45 years (IIQ 34-55), with 289 (51.7%) female and 438 (81.4%) from the capital. Of the reports with metaplasia, 46 (8.2%) had Helicobacter pylori, 30 (5.3%) Barrett’s esophagus and 14 (2.6%) had gastric atrophy associated with bacteria, however there was no significant association with H. pylori. The association of metaplasia with esophagitis, eosinophilic esophagitis and adenomatous polyp was statistically significant (p<0.001). Together, we observed a lower risk of metaplasia in the presence of esophagitis (RR: 0.44; 95%CI: 0.36-0.55) and higher in the presence of Eosinophils >=15 eos/CGA (RR: 3.27; 95%CI %: 1.70-6.62). Conclusion: We have no evidence of a relationship between esophageal metaplasia and H.pylori. The absence of esophagitis and the presence of Eosinophils >=15 eos/CGA is associated with an increased risk of metaplastic transformation.